KARAKTERISTIK KIMIA, MIKROBIOLOGI, DAN ORGANOLEPTIK PADA PRODUK JUS JERUK - Marfirah, Laila; Maryati, Sri; Anggriawin, Mirza (Fakultas Pertanian, Universitas Janabadra, 2023)
Fruit juice drinks are drinks obtained by mixing drinking water, fruit juice/a mixture of unfermented fruit juices, with other parts of one or more types of fruit, with or without the addition of sugar, other permitted food ingredients. This research aims to obtain data and information regarding the chemical, microbiological and organoleptic properties of orange juice samples (A), (B) and (C). The sampling technique was carried out by purchasing juice samples from 3 vendors, namely juice (A), juice(B) and juice(C). The sample criteria taken were orange juice from Siamese orange raw materials with the addition of water and sugar and sampling was carried out three times, with a production interval of once a week. The results of the research for chemical analysis of the three juice samples tested in the form of TPT, pH and vitamin C levels met the SNI standards set for the fruit juice drink category. Vitamin C levels are greatly influenced by the addition of water volume as a solvent. Bacterial culture testing using the ALT method on all of the orange juice samples tested had the number of microorganism colonies below the threshold set by SNI and was safe for consumption, namely below 10×10² CFU/ mL . Salmonella microbial contamination. Sp was identified positively only in the orange juice sample (A) and E. coli microbial contamination was positively identified in two orange juice samples, namely samples (A) and (B). The results of the organoleptic test using the hedonic method for taste, color, aroma parameters and the overall value scale ranged from 2.5 – 3.4 in the somewhat like category. Overall, the organoleptic tests of the three juice samples tested by the panelists preferred the orange juice sample (C). Keywords: Orange juice, microbiology, organoleptic, vitamin C INTISARIMinuman sari buah adalah minuman yang diperoleh dengan mencampur air minum, sari buah/campuran sari buah yang tidak difermentasi, dengan bagian lain dari satu jenis buah atau lebih, dengan atau tanpa penambahan gula, bahan pangan lainnya yang diizinkan. Penelitian ini bertujuan untuk memperoleh data dan informasi mengenai sifat kimia, mikrobiologi dan organoleptik jus jeruk sampel (A), (B) dan (C). Teknik sampling dilakukan pembelian sampel jus pada 3 vendor yaitu Jus (A), jus (B) dan Jus (C). Kriteria sampel yang diambil adalah jus jeruk dari bahan baku jeruk siam dengan penambahan air dan gula serta pengambilan sampel dilakukan sebanyak tiga kali, dengan selang waktu produksi seminggu sekali. Hasil penelitian untuk analisis kimia dari ketiga sampel jus yang di uji berupa TPT, pH dan kadar vitamin C memenuhi standar SNI yang ditetapkan untuk katagori minuman sari buah. Kadar vitamin C sangat dipengaruhi oleh penambahan volume air sebagai bahan pelarut. Pengujian kultur bakteri dengan metode ALT pada sampel jus jeruk yang diuji seluruhnya memiliki jumlah koloni mikroorganisme di bawah ambang batas yang ditetapkan SNI dan aman untuk dikonsumsi yaitu dibawah 10 10² CFU/mL. Cemaran mikroba Salmonella. Sp teridentifikasi positif hanya pada sampel jus jeruk (A) dan cemaran mikroba E. coli teridentifikasi positif pada dua sampel jus jeruk yaitu sampel (A) dan (B). Hasil uji organoleptik dengan metode hedonik untuk parameter rasa, warna, aroma dan keseluruhan skala nilai berkisar 2,5 – 3,4 masuk dalam katagori agak suka. Secara keseluruhan uji organoleptik dari ketiga sampel jus yang diuji panelis lebih menyukai sampel jus jeruk (C). Kata kunci: Jus jeruk, mikrobiologi, organoleptik, vitamin C